DYNAMIC OF DEPRESSIVE DETERIORATIONS IN WOMEN WITH DENTAL SURGICAL OPERATIONS - Balykov, V.V.; Babov, E.D.; Puzyryov, A.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In women of 53,1+3,9 years old who underwent dental surgical intervention, the administration of frozened placenta pharmacon (FPP) caused the net reduction of depressive state manifestations. This effect was registered after 10 days from the moment of treatment and was pronounced in comparison with the group of age- matched control women who were only operated on without FPP administration. This period of time the blood level of tumor necrosing factor-a was 1,95 times fold decreased in comparison with that one detected in group of women with traditional treatment. The obtained data are in favor of the rationality of FPP usage in patients who are treated with dental surgery intervention.